2021
DOI: 10.3390/diagnostics11091543
|View full text |Cite
|
Sign up to set email alerts
|

Fetal Presentation of Mediastinal Immature Teratoma: Ultrasound, Autopsy and Cytogenetic Findings

Abstract: Teratomas are the most common congenital tumors, occurring along the midline or paraxial sites, or uncommonly, the mediastinum. Teratomas are classified as mature, containing only differentiated tissues from the three germinal layers; and immature, which also present with neuroectodermal elements, ependymal rosettes, and immature mesenchyme. Herein, we describe a new case of fetal mediastinal immature teratoma detected at 21 weeks of gestational age (wga) + 1 day with thorough cytogenetic analysis. Ultrasound … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 39 publications
0
16
0
Order By: Relevance
“…Intrapericardial teratoma was first described by Joel et al [12] in 1890, after which it has been rarely reported. Pilu et al [1] reported 16 cases of intrapericardial teratoma diagnosed by antenatal ultrasound up to 2021, 12 of which complicated by NIFH. Only four cases were diagnosed before 22 weeks (gestational age ranged from 20 to 38 weeks, median 28 weeks), with survival in two (C-section performed at 25 weeks in one case and at 33 weeks in the other), and EXIT was performed in 1/16 cases.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Intrapericardial teratoma was first described by Joel et al [12] in 1890, after which it has been rarely reported. Pilu et al [1] reported 16 cases of intrapericardial teratoma diagnosed by antenatal ultrasound up to 2021, 12 of which complicated by NIFH. Only four cases were diagnosed before 22 weeks (gestational age ranged from 20 to 38 weeks, median 28 weeks), with survival in two (C-section performed at 25 weeks in one case and at 33 weeks in the other), and EXIT was performed in 1/16 cases.…”
Section: Discussionmentioning
confidence: 99%
“…Intrapericardial teratoma is a rare, potentially fatal tumor derived from endodermal, mesodermal, and ectodermal cell lines and usually diagnosed in the perinatal period [1, 2]. Most are of vascular origin and arise from the aorta or pulmonary artery [3], where they may impair thoracic blood and lymphatic circulation and cause non-immune fetal hydrops (NIFH).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Systematic literature reviews and metanalyses (SLRs) conducted according to the PRISMA guidelines (including an evidence-based minimum set of items for reporting) ( , accessed on 8 May 2021) are increasingly important in health care, keeping medical doctors up to date, and also representing the background for developing clinical guidelines/trials, as well as the justification for financial supports of research projects. Usually conducted by multidisciplinary teams, SLRs performed according to these guidelines could be applicable in various topics/contexts, improving the research quality not only of pure meta-analyses but also of SLRs applied to case report/series [ 215 , 216 , 217 , 218 , 219 , 220 , 221 , 222 , 223 , 224 , 225 , 226 , 227 , 228 , 229 , 230 , 231 , 232 , 233 , 234 , 235 , 236 , 237 , 238 , 239 , 240 , 241 , 242 , 243 , 244 , 245 , 246 , 247 , 248 , 249 , 250 , 251 , 252 , 253 , 254 , 255 , 256 , …”
Section: Discussionmentioning
confidence: 99%
“…They highlight various subtopics, including: PD-L1 immunohistochemical expression in PC cases, with discussion of pre-analytical and interpretation variables; correlations of PD-L1 expression with clinic-pathological features in PC patients; genetic and epigenetic regulation of PD-L1; data of pre-clinical studies (cell lines, mouse models) about the effects of experimental treatments on PD-L1 expression in PC cells; investigated correlations of PD-L1 expression with the status of mismatch repair system, BRCA, PTEN and other main genes in PC; PD-L1 expression in liquid biopsy samples; information of clinical trials, etc. We address the Readers to the other papers for further details on these subtopics [259][260][261][262][263][264][265][266][267][268][269][270][271][272][273][274][275][276].…”
Section: Methodsmentioning
confidence: 99%